Neurodegenerative changes and neuroapoptosis induced by systemic lipopolysaccharide administration are reversed by dexmedetomidine treatment in mice. (3rd April 2017) - Ning, Qiaoqing; Liu, Zhaoguo; Wang, Xiuhua; Zhang, Ruyi; Zhang, Jing; Yang, Meizi; Sun, Hongliu; Han, Fang; Zhao, Wenxiang; Zhang, Xiuli
Abstract: Background: Sepsis-associated encephalopathy (SAE) is a frequent and nasty complication of sepsis, associated with patients increased risk of death and long-term brain dysfunctions. Objective: This study aimed to explore the effect of dexmedetomidine (Dex), an anesthetic adjuvant, on the development of SAE. Methods: Lipopolysaccharide (LPS, 10 mg/kg) was intraperitoneally injected to male BALB/c mice to induce sepsis. Dex (25 μg/kg) was given intraperitoneally immediately after LPS injection. Levels of TNF-α, IL-1β, malondialdehyde (MDA) and reactive oxygen species (ROS) were detected in mice brains tissue eight hours later after drug administration. Hematoxylin and eosin (HE) staining was used to detect brain pathologic change. We also detected apoptosis using terminal deoxynucleotidyl transferase-mediated dUTP nick end-labeling assay and Bcl-2, Bax, Caspase-3 expressions by western blot. Results: Levels of TNF-α, IL-1β, MDA and ROS were increased in the brain tissue after LPS treatment, indicating that LPS injection resulted in increased brain inflammation and elevated oxidative stress. We further found a large quantity of degenerative neurons widespread in hippocampal CA1, CA3 regions and cerebral cortex according to HE staining. Dex could significantly decrease brain inflammation and oxidative stress by decreasing the levels of TNF-α, IL-1β, MDA and ROS, and ameliorate neurodegenerative changes. The associated results also demonstrated that Dex treatment ameliorated the LPS-induced neuronal apoptosis, probably by upregulating the Bcl-2 expression and downregulating the Bax expression. Conclusion: Our results indicated that Dex could reverse neurodegenerative changes and neuroapoptosis in mice brain of septic mice induced by LPS through anti-inflammatory and antiapoptotic effects.